1991
DOI: 10.1001/archderm.1991.01680100117017
|View full text |Cite
|
Sign up to set email alerts
|

Multiple Papules on the Leg

Abstract: A 45-year-old white woman was referred to the department of dermatology for evaluation of asymptomatic lesions on her right lower leg. The lesions had first appeared approximately 8 years earlier and had remained unchanged. The patient denied fever or constitutional symptoms. Her other medical problems included rheumatoid arthritis and type II diabetes mellitus.The findings of the physical examination revealed approximately 20 discrete, 4-to 6-mm firm, nontender, erythematous, blanchable papules on the anterol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

1995
1995
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 6 publications
0
4
0
Order By: Relevance
“…Pain can be spontaneous or can occur after exposure to cold, pressure, injury or emotional stress [1,12,13]. Our patients, however, reported little pain.…”
Section: Discussionmentioning
confidence: 74%
“…Pain can be spontaneous or can occur after exposure to cold, pressure, injury or emotional stress [1,12,13]. Our patients, however, reported little pain.…”
Section: Discussionmentioning
confidence: 74%
“…Pain can be spontaneous or occur on exposure to cold, pressure, injury or emotional stress. 5,6,7 Our case is a presentation in a 36 year old male with family history of similar lesions in his brother. Our patient had visited the OPD in view of cosmetic concern, and pain.…”
Section: Discussionmentioning
confidence: 84%
“…Multiple piloleiomyoma, most common type of cutaneous leiomyoma, are small, firm, red or brown intradermal nodules arranged in a group or linear pattern, primarily affecting the trunk and extremities but may occur on the face and neck and rarely in the mouth. 5 We extensively search for large series studies on leiomyoma cutis on internet but we found only some studies and not found any study in which more than 40 case were reported. Here we describe some studies on cutaneous leiomyoma.…”
Section: Case Reportmentioning
confidence: 99%